From Comic Strips to Graphic Novels - Stein, Daniel,Thon, Jan-Noël (De Gruyter, 2015)
This essay collection examines the theory and history of graphic narrative as one of the most interesting and versatile forms of storytelling in contemporary media culture. Its contributions test the applicability of narratological concepts to graphic narrative, examine aspects of graphic narrative beyond the 'single work', consider the development of particular narrative strategies within individual genres, and trace the forms and functions of graphic narrative across cultures. Analyzing a wide range of texts, genres, and narrative strategies from both theoretical and historical perspectives, the international group of scholars gathered here offers state-of-the-art research on graphic narrative in the context of an increasingly postclassical and transmedial narratology.This is the revised second edition of From Comic Strips to Graphic Novels, which was originally published in the Narratologia series
10.1515/9783110427660
Keywords: Comic books; strips; etc / History and criticism; Graphic novels / History and criticism; Narration (Rhetoric); Comic; Comics; Graphic Novel; Narratology; Erzähltechnik; Erzähltheorie; Comicroman; LITERARY CRITICISM / European / General